Measurement of ammonia inhibition of microbial activity in biological wastewater treatment process using dehydrogenase assay - Lee, SM; Jung, JY; Chung, YC (KLUWER ACADEMIC PUBL, 2000)
Ammonia inhibition of microbial activity in biological wastewater treatment process, studied by using a dehydrogenase assay with specific inhibitor of nitrification, strongly correlated with the total amount of ammonia and the pH of wastewater. Total ammonia concentration, as well as free ammonia, is an important factor in ammonia inhibition and should be included to obtain an accurate measurement. Nitrifying bacteria were more sensitive than heterotrophic bacteria when the ammonia concentration went over above 3000 mg l(-1).